The use of teams games tournament learning to increase students' learning outcomes in classification of living things - Rahmah, Fajriani; Sirait, Silvia Hanna Kusuma; Nunaki, Jan Hendriek (Univeritas Papua, 2023)
This research aims to improve student learning outcomes through the use of teams games tournament (TGT) learning. This classroom action research was carried out in class VII B of SMP Negeri 10 Manokwari. The research subjects were 18 students. The cycle was carried out as much as and and a test to measure student learning outcomes. The results of the study show that the use of TGT learning can improve student learning outcomes. It is proven by the percentage of the average classical completeness score of students' learning outcomes in the first cycle of 77.8% and increased in the second cycle to 88.8%. The findings indicate that student learning outcomes has met the 75% classical standard. Student activity has also increased. Based on the results of the research that has been done, it can be concluded that the application of TGT can improve student learning outcomes.